Forschungszusammenarbeit China-Deutschland: Interdisziplinäre Zugänge und transkulturelle Perspektiven - Stroth, Maria; Robak, Steffi; Zizek, Boris; Hu, Chunchun (transcript, 2020)
Status quo and opportunities of Sino-German cooperation in science – education, culture and comparative perspectives.